2022
DOI: 10.1111/tct.13477
|View full text |Cite
|
Sign up to set email alerts
|

Are 3D printed models acceptable in assessment?

Abstract: Background: Three-dimensional (3D) printed models are increasingly used in undergraduate anatomy teaching. However, their role and value in anatomy assessment remains under consideration. The aim of this study was to evaluate student and educator perspectives on acceptability of using novel 3D printed heart models for assessment. Methods:We used printed 3D models of the heart for first-year medical students, in small group teaching, formative assessment and revision at home. We adopted a mixed methods approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The main drawbacks were related to design: stiffness [ 80 ], consistency [ 28 , 62 ], lack of detail or transparency [ 28 , 30 , 34 , 45 , 48 , 62 , 64 , 81 ], overly bright colours [ 45 ], and fragility [ 71 ]. Other drawbacks were the loss of information [ 30 , 76 ], long time needed for image segmentation [ 36 , 52 , 57 , 58 , 74 ], printing time [ 57 , 63 , 66 , 67 ], lack of anatomical variability [ 25 ] and the high cost [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main drawbacks were related to design: stiffness [ 80 ], consistency [ 28 , 62 ], lack of detail or transparency [ 28 , 30 , 34 , 45 , 48 , 62 , 64 , 81 ], overly bright colours [ 45 ], and fragility [ 71 ]. Other drawbacks were the loss of information [ 30 , 76 ], long time needed for image segmentation [ 36 , 52 , 57 , 58 , 74 ], printing time [ 57 , 63 , 66 , 67 ], lack of anatomical variability [ 25 ] and the high cost [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested that advanced printing technologies such as SLS should be used whenever possible to improve the 3DPAM’s accuracy [ 38 ]. The help of a professional was required to make the 3DPAM; the most requested professionals were an engineer [ 72 ], radiologist, [ 75 ] graphic designer, [ 43 ] and anatomist [ 25 , 28 , 51 , 57 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of 3DP models bridges the gap between two-dimensional (2D) imaging and realistic anatomy, as it accurately reproduces anatomical structures and pathologies, thereby providing more tangible information than conventional imaging data [ 19 ]. 3DP models also appear to be a significantly more useful and cost-effective technique than traditional cadaveric models in medical education [ 20 ], such as those used in undergraduate dentistry training [ 4 ], urology residents [ 21 ], first-year medical students [ 22 ], craniofacial traumas [ 23 ], oral and cranio-maxillofacial surgery [ 24 ]. However, recent SBME changes regarding 3DP models have focused only on undergraduate medical education [ 25 ].…”
Section: Introductionmentioning
confidence: 99%